Pengaruh Kepemilikan Institusional, Profitabilitas dan Tingkat Volatilitas Saham terhadap Nilai Perusahaan - Sabilil Muttaqien; Dedi Kusmayadi; Edy Suroso (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine and analyze the influence of institutional ownership, profitability and stock volatility on company value. The study was conducted on companies indexed by the Kompas 100 shares for 2018 - 2023. The sample size was set at 26 companies with observation data from 2018 to 2023. The type of data used was secondary data in the form of panel data. The data analysis technique used is multiple linear regression with the Eviews application. The results of this research show that, 1) Institutional ownership has a stable trend, while profitability, the level of share volatility and company value, has a decreasing trend; 2) Institutional ownership, profitability and stock volatility simultaneously influence company value; 3) Institutional ownership partially has a positive but not significant effect on firm value; 4) Profitability partially has a negative and significant effect on company value; 5) The level of share volatility partially has a positive and significant effect on company value